Lithium-ion battery and electric device
Patent Information
- Application Number
- CN202611314744.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]锂离子电池- 20℃及以下的低温环境中,但电解液在低温下粘度急剧升高、离子电导率骤降,导致电池内阻大幅攀升,放电容量显著衰减;在45℃及以上的高温环境中,但电解液在高温下与正负极的副反应加剧,固体电解质界面膜、正极-电解液界面膜持续生长增厚,造成电池循环寿命急剧缩短
负极活性物质层采用表层孔隙率高、底层孔隙率低的梯度分布设计,这样,对高低温性能实现双向适配,并且同时将孔隙率梯度与压实密度的比值控制在3.5至5.5范围内,可精准调控梯度幅度,既保证表层具备足够的电解质浸润空间与传质能力,又避免梯度过大导致底层离子传输受阻、或梯度过小无法发挥梯度调控作用,实现极片结构在低温传质效率与高温结构稳定性之间的最优平衡。
Smart Images

Figure CN123018084A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, specifically to a lithium-ion battery and an electrical device. Background Technology
[0002] Currently, with the widespread application of lithium-ion batteries in new energy vehicles, energy storage systems, and portable electronic devices, the requirements for battery miniaturization, energy density, and thermal safety performance are continuously increasing. In some extreme scenarios, lithium-ion batteries also need to have high capacity and good rate performance to ensure smooth operation.
[0003] In low-temperature environments of -20℃ and below, the viscosity of the electrolyte increases sharply and the ionic conductivity drops sharply at low temperatures, resulting in a significant increase in the battery's internal resistance and a significant decrease in discharge capacity. In high-temperature environments of 45℃ and above, the side reactions between the electrolyte and the positive and negative electrodes intensify at high temperatures, and the solid electrolyte interface film and the positive electrode-electrolyte interface film continue to grow and thicken, causing a sharp reduction in the battery's cycle life.
[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of this application, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention
[0005] In the process of developing the embodiments of this disclosure, it was further discovered that in related technologies, improving low-temperature or high-temperature performance, such as by using low-viscosity solvent components, reduces the overall viscosity of the electrolyte, increases low-temperature ionic conductivity, and improves low-temperature rate discharge performance, is possible. However, low-viscosity solvents usually have insufficient high-temperature stability, which will aggravate electrolyte decomposition and interfacial side reactions at high temperatures, resulting in a decrease in high-temperature cycle performance. For example, by adding a large amount of film-forming additives, a stable interfacial layer can be constructed on the electrode surface to suppress high-temperature side reactions and extend cycle life. However, excessive film-forming components will form a thick interfacial film with high impedance at low temperatures, further increasing the low-temperature interfacial impedance of the battery and deteriorating low-temperature discharge performance.
[0006] To provide a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended as a general commentary, nor is it intended to identify key / important components or describe the scope of protection of these embodiments, but rather as a prelude to the detailed description that follows.
[0007] This disclosure provides a lithium-ion battery and an electrical device that can simultaneously improve the low-temperature rate performance and high-temperature cycle performance of the lithium-ion battery.
[0008] In some embodiments, the lithium-ion battery includes a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode active material layer includes artificial graphite material and hard carbon. The negative electrode active material layer has a porosity gradient in the thickness direction and satisfies the following relationship: 3.5≤(ε s -ε i ) / P≤5.5; Where, ε s ε represents the surface porosity of the negative electrode sheet, expressed as a percentage (%). i P represents the bottom layer porosity of the negative electrode sheet, expressed as %, while P represents the compacted density of the negative electrode sheet, expressed as g / cm³. 3 ; Electrolytes include organic solvents, lithium salts, and additives, wherein the organic solvents include ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether; the lithium salts include lithium hexafluorophosphate and lithium difluorosulfonylimide; and the additives include ethylene carbonate, ethylene sulfate, and tris(trimethylsilyl)borate.
[0009] In some embodiments, the mass ratio of artificial graphite material to hard carbon is 85:15 to 95:5.
[0010] In some embodiments, the surface porosity of the negative electrode sheet is 28% to 35%, and the bottom porosity of the negative electrode sheet is 20% to 28%.
[0011] In some embodiments, the surface layer of the negative electrode sheet extends from the surface of the negative electrode sheet to 1 / 3 of the thickness of the negative electrode active material layer, and the bottom layer of the negative electrode sheet extends from 2 / 3 of the thickness of the negative electrode active material layer to the interface between the current collector and the negative electrode active material layer.
[0012] In some embodiments, the compaction density of the negative electrode sheet is 1.60 g / cm³. 3 Up to 1.75 g / cm 3 .
[0013] In some embodiments, the volume ratio of ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether is from 10:50:20:20 to 20:60:10:10.
[0014] In some embodiments, the concentration of lithium hexafluorophosphate is from 0.6 mol / L to 1.0 mol / L, and the concentration of lithium difluorosulfonylimide is from 0.2 mol / L to 0.5 mol / L.
[0015] In some embodiments, vinylene carbonate accounts for 0.5% to 2.0% of the total mass of the electrolyte, vinyl sulfate accounts for 0.5% to 2.5% of the total mass of the electrolyte, and tris(trimethylsilyl)borate accounts for 0.3% to 1.5% of the total mass of the electrolyte.
[0016] In some embodiments, the lithium-ion battery is formed through three sequential charging stages, wherein the ambient temperature and the charging rate increase in each of the three stages.
[0017] In some embodiments, the formation process of a lithium-ion battery includes the following three charging stages: Phase 1: Under the first temperature environment, constant current charging at the first charging rate for a preset duration; Second stage: Under the second temperature environment, charge at a constant current at a second charging rate to the first preset voltage; The third stage: Under the third temperature environment, constant current charging is performed at the third charging rate until the second preset voltage is reached, and then constant voltage charging is switched until the charging current drops to the cutoff current, thus completing the formation.
[0018] In some embodiments, in the first stage, the first temperature is -10°C to 5°C, the first charging rate is 0.03C to 0.08C, and the preset duration is 1.5h to 3h; in the second stage, the second temperature is 20°C to 30°C, the second charging rate is 0.1C to 0.2C, and the first preset voltage is 3.4V to 3.6V; in the third stage, the third temperature is 40°C to 50°C, the third charging rate is 0.2C to 0.3C, the second preset voltage is 4.15V to 4.25V, and the cutoff current is 0.02C to 0.05C.
[0019] In some embodiments, the electrical device includes a lithium-ion battery as described in the foregoing embodiments.
[0020] The lithium-ion battery and power-consuming device provided in this disclosure can achieve the following technical effects: The negative electrode active material layer adopts a gradient distribution design with high porosity on the surface and low porosity on the bottom. This allows for bidirectional adaptation to high and low temperature performance. At the same time, the ratio of porosity gradient to compaction density is controlled within the range of 3.5 to 5.5, which can precisely control the gradient amplitude. This ensures that the surface layer has sufficient electrolyte wetting space and mass transfer capacity, while avoiding the gradient being too large, which would hinder ion transport in the bottom layer, or too small, which would not play a gradient control role. This achieves the optimal balance between low-temperature mass transfer efficiency and high-temperature structural stability of the electrode structure.
[0021] Furthermore, in the electrolyte, organic solvents composed of ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether can broaden the low-temperature operating range of the electrolyte and participate in the construction of the interfacial film, significantly improving the high-temperature oxidation and reduction stability of the interfacial film. The use of lithium hexafluorophosphate and lithium difluorosulfonylimide can significantly improve the low-temperature conductivity of the electrolyte, and their decomposition products can also participate in the modification of the interfacial film. The synergistic film formation of vinylene carbonate, ethylene sulfate, and tris(trimethylsilyl)borate can form thin, dense, low-impedance, and structurally stable interfacial films on the positive and negative electrode surfaces.
[0022] The above general description and the description below are exemplary and illustrative only and are not intended to limit this application. Attached Figure Description
[0023] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations and drawings do not constitute a limitation on the embodiments. Elements having the same reference numerals in the drawings are shown as similar elements. The drawings are not to be scaled. And wherein: Figure 1 This is a schematic diagram of the structure of a lithium-ion battery provided in an embodiment of this disclosure; Figure 2 This is a schematic diagram of the structure of the winding core provided in the embodiments of this disclosure; Figure 3 This is a schematic diagram of the structure of a lithium-ion battery provided in an embodiment of this disclosure.
[0024] Figure label: 1. Positive terminal; 10. Cell; 11. Positive terminal post; 12. Negative terminal; 2. Casing; 3. Negative electrode plate; 4. Separator; 5. Positive electrode plate. Detailed Implementation
[0025] To provide a more detailed understanding of the features and technical content of the embodiments of this disclosure, the implementation of the embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. The accompanying drawings are for illustrative purposes only and are not intended to limit the embodiments of this disclosure. In the following technical description, for ease of explanation, several details are used to provide a full understanding of the disclosed embodiments. However, one or more embodiments may still be implemented without these details. In other cases, well-known structures and devices may be simplified in their depiction to simplify the drawings.
[0026] The terms "first," "second," etc., used in the specification, claims, and accompanying drawings of this disclosure are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate for the embodiments of this disclosure described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion.
[0027] In this disclosure, the terms "upper," "lower," "inner," "middle," "outer," "front," and "rear," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. These terms are primarily for better description of the embodiments of this disclosure and their implementations, and are not intended to limit the indicated devices, elements, or components to having a specific orientation, or to require them to be constructed and operated in a specific orientation. Furthermore, some of the aforementioned terms may be used to indicate other meanings besides orientation or positional relationship; for example, the term "upper" may in some cases indicate a dependency or connection relationship. Those skilled in the art can understand the specific meaning of these terms in the embodiments of this disclosure according to the specific circumstances.
[0028] Furthermore, the terms "set up," "connect," and "fix" should be interpreted broadly. For example, "connection" can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, components, or parts. Those skilled in the art can understand the specific meaning of the above terms in the embodiments of this disclosure according to the specific circumstances.
[0029] Unless otherwise stated, the term "multiple" means two or more.
[0030] In this embodiment of the disclosure, the character " / " indicates that the objects before and after it are in an "or" relationship. For example, A / B means: A or B.
[0031] The term "and / or" describes an association between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or A and B.
[0032] It should be noted that, unless otherwise specified, the embodiments and features described in the present disclosure can be combined with each other.
[0033] This disclosure provides a lithium-ion battery, including a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode active material layer includes artificial graphite material and hard carbon. The negative electrode active material layer has a porosity gradient in the thickness direction and satisfies the following relationship: 3.5≤(ε s -ε i ) / P≤5.5; Where, ε s ε represents the surface porosity of the negative electrode sheet, expressed as a percentage (%). iP represents the bottom layer porosity of the negative electrode sheet, expressed as %, while P represents the compacted density of the negative electrode sheet, expressed as g / cm³. 3 ;ε s and ε i Simply substitute the value before the % symbol into the calculation.
[0034] Electrolytes include organic solvents, lithium salts, and additives, wherein the organic solvents include ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether; the lithium salts include lithium hexafluorophosphate and lithium difluorosulfonylimide; and the additives include ethylene carbonate, ethylene sulfate, and tris(trimethylsilyl)borate.
[0035] The lithium-ion battery provided in this embodiment adopts a gradient distribution design with high porosity on the surface and low porosity on the bottom layer in the negative electrode active material layer. This achieves bidirectional adaptation to high and low temperature performance, and at the same time controls the ratio of porosity gradient to compaction density within the range of 3.5 to 5.5. The gradient amplitude can be precisely controlled, which ensures that the surface layer has sufficient electrolyte wetting space and mass transfer capacity, while avoiding the gradient being too large, which would hinder ion transport in the bottom layer, or the gradient being too small, which would not play a gradient control role. This achieves the optimal balance between low-temperature mass transfer efficiency and high-temperature structural stability of the electrode structure.
[0036] Furthermore, in the electrolyte, organic solvents composed of ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether can broaden the low-temperature operating range of the electrolyte and participate in the construction of the interfacial film, significantly improving the high-temperature oxidation and reduction stability of the interfacial film. The use of lithium hexafluorophosphate and lithium difluorosulfonylimide can significantly improve the low-temperature conductivity of the electrolyte, and their decomposition products can also participate in the modification of the interfacial film. The synergistic film formation of vinylene carbonate, ethylene sulfate, and tris(trimethylsilyl)borate can form thin, dense, low-impedance, and structurally stable interfacial films on the positive and negative electrode surfaces.
[0037] In the embodiments of this disclosure, the surface porosity of the negative electrode is relatively high, which allows for the storage of more electrolyte, constructs sufficient lithium-ion diffusion and mass transfer channels, effectively alleviates the problems of increased electrolyte viscosity and decreased ionic conductivity in environments at -20°C and below, reduces concentration polarization during high-current discharge, ensures rapid lithium-ion insertion / extraction at 3C and above rates, and suppresses significant decay of low-temperature discharge capacity.
[0038] In the embodiments of this disclosure, the bottom layer of the negative electrode sheet has low porosity, which improves the structural compactness of the current collector side electrode sheet, reduces the side reaction contact sites between the electrolyte and the active material and the current collector during high-temperature cycling, enhances the overall structural stability of the electrode sheet, inhibits the pulverization and shedding of the active material during long-term cycling, and avoids the continuous growth and thickening of the interface film.
[0039] In this embodiment, the graphite in the negative electrode provides high capacity and a low potential plateau, while hard carbon provides abundant microporous defect sites, resulting in faster low-temperature lithium intercalation kinetics. Here, by controlling the drying temperature gradient during negative electrode coating, a higher surface porosity is achieved, which facilitates rapid electrolyte wetting and Li-ionization at low temperatures. + Transport; resulting in low porosity in the bottom layer, which is beneficial for increasing compaction density and electronic conductivity.
[0040] In the embodiments of this disclosure, ethyl methyl carbonate serves as a low-viscosity base solvent in the organic solvent of the electrolyte, ensuring the basic low-temperature ionic conductivity of the electrolyte. The introduction of fluoroethylene carbonate and hydrofluoroether not only further broadens the low-temperature operating range of the electrolyte by taking advantage of the low freezing point of the fluorinated solvent, but also participates in the construction of the interfacial film, significantly improving the high-temperature oxidation and reduction stability of the interfacial film.
[0041] In this embodiment of the disclosure, lithium hexafluorophosphate and lithium bisfluorosulfonylimide are combined in the lithium salt of the electrolyte: lithium bisfluorosulfonylimide has high degree of dissociation and excellent low-temperature ion mobility, which can significantly improve the low-temperature conductivity of the electrolyte, and its decomposition products can also participate in the modification of the interface film; the combination of the two not only makes up for the shortcomings of insufficient low-temperature conductivity of lithium hexafluorophosphate alone, but also avoids the problem of insufficient high-temperature stability of single lithium salt.
[0042] In this embodiment, vinylene carbonate, vinyl sulfate, and tris(trimethylsilyl)borate are used as additives in the electrolyte to form a thin, dense, low-impedance, and structurally stable interface film on the positive and negative electrode surfaces. The interface film formed by this composite system exhibits lower lithium-ion transport impedance at low temperatures, thus not deteriorating low-temperature discharge performance; at high temperatures, it effectively blocks direct contact between the electrolyte and the electrode, inhibiting continuous thickening of the interface film and continuous decomposition of the electrolyte during cycling, simultaneously achieving both low-temperature interface charge transfer efficiency and high-temperature interface passivation effect.
[0043] In some embodiments, the mass ratio of artificial graphite material to hard carbon is 85:15 to 95:5.
[0044] In some embodiments, the median particle size D of the artificial graphite material 50 Larger than the median particle size D of hard carbon materials 50 .
[0045] In some embodiments, the median particle size D of artificial graphite 50 The size ranges from 10 μm to 18 μm.
[0046] In some embodiments, the median particle size D of hard carbon 50 The size ranges from 5μm to 10μm.
[0047] In some embodiments, the surface porosity of the negative electrode sheet is 28% to 35%, the bottom porosity is 20% to 28%, and the compacted density of the negative electrode sheet is 1.60 g / cm³. 3 Up to 1.75 g / cm 3 .
[0048] In some embodiments, the surface layer of the negative electrode sheet extends from the surface of the negative electrode sheet to 1 / 3 of the thickness of the negative electrode active material layer, and the bottom layer of the negative electrode sheet extends from 2 / 3 of the thickness of the negative electrode active material layer to the interface between the current collector and the negative electrode active material layer.
[0049] In some embodiments, the volume ratio of ethylene carbonate (EC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), and hydrofluoroether (HFE) is from 10:50:20:20 to 20:60:10:10.
[0050] In some embodiments, the concentration of lithium hexafluorophosphate (LiPF6) is from 0.6 mol / L to 1.0 mol / L, and the concentration of lithium bisfluorosulfonyl imide (LiFSI) is from 0.2 mol / L to 0.5 mol / L.
[0051] In some embodiments, vinylene carbonate (VC) accounts for 0.5% to 2.0% of the total mass of the electrolyte, vinyl sulfate (DTD) accounts for 0.5% to 2.5% of the total mass of the electrolyte, and tris(trimethylsilyl)borate (TMSB) accounts for 0.3% to 1.5% of the total mass of the electrolyte.
[0052] In some embodiments, the lithium-ion battery is formed through three sequential charging stages, wherein the ambient temperature and the charging rate increase in each of the three stages.
[0053] In some embodiments, the formation process of a lithium-ion battery includes the following three charging stages: The process includes: a first stage: charging at a constant current at a first charging rate for a preset duration under a first temperature environment; a second stage: charging at a constant current at a second charging rate to a first preset voltage under a second temperature environment; and a third stage: charging at a constant current at a third charging rate to a second preset voltage under a third temperature environment, then switching to constant voltage charging until the charging current drops to the cutoff current, thus completing the formation process.
[0054] In the embodiments disclosed herein, the first stage of low-temperature, low-rate charging can slowly and uniformly generate initial SEI crystal nuclei on the surface of the negative electrode, avoiding the problems of uneven film formation and local thick films at high rates. This allows LiFSI to be preferentially reduced to form an inorganic underlayer rich in LiF.
[0055] In this embodiment of the disclosure, the second stage involves medium-rate charging at room temperature to guide the uniform growth of the interfacial film, forming a continuous film substrate with a suitable thickness; in this way, VC and DTD can polymerize to form an organic intermediate layer.
[0056] In this embodiment, the third stage of high-temperature, high-rate constant current to constant voltage charging promotes further densification of the interface film and completes the full-charge formation of the battery. In this way, the FEC and TMSB can form a protective outer layer containing BO bonds and CF bonds, which, compared to conventional single-stage room temperature formation, can only form a disordered mixed SEI film.
[0057] In some embodiments, in the first stage, the first temperature is -10°C to 5°C, the first charging rate is 0.03C to 0.08C, and the preset duration is 1.5h to 3h; in the second stage, the second temperature is 20°C to 30°C, the second charging rate is 0.1C to 0.2C, and the first preset voltage is 3.4V to 3.6V; in the third stage, the third temperature is 40°C to 50°C, the third charging rate is 0.2C to 0.3C, the second preset voltage is 4.15V to 4.25V, and the cutoff current is 0.02C to 0.05C.
[0058] In this embodiment, the lithium-ion battery is formed through three sequential charging stages, with the ambient temperature and charging rate increasing progressively in each stage. This ensures a precise fit with the negative electrode and electrolyte, further improving the uniformity of the interface film thickness, resulting in a dense structure and controllable impedance. It possesses excellent lithium-ion conductivity to adapt to low-temperature, high-rate discharge, and reliable passivation barrier capability to support high-temperature, long-cycle operation.
[0059] Therefore, through the above optimized design, a gradient SEI film with an inner dense inorganic structure and an outer organic porous structure can be formed on the negative electrode side, while a stable CEI film rich in Li3PO4F and CF bonds can be formed on the positive electrode side. This dual-interface film does not increase additional impedance at low temperatures and does not dissolve or remodel at high temperatures, thus achieving good low-temperature rate performance and high-temperature cycling performance simultaneously.
[0060] In some embodiments, the lithium-ion battery of this application, when continuously discharged at a rate of 3C or higher in an environment with a temperature of -20°C or below, retains a capacity of Q1 ≥ 68%.
[0061] In some embodiments, the lithium-ion battery of this application retains a capacity of Q2 ≥ 80% after 1000 cycles at a 1C rate in an environment with a temperature of 45°C or above.
[0062] In some embodiments, the lithium-ion battery of this application has an AC internal resistance R at 25°C. ac ≤8mΩ, DC internal resistance R dc≤15mΩ.
[0063] In some embodiments, the lithium-ion battery of this application can support pulse discharge greater than 10C.
[0064] In some embodiments, the lithium-ion battery of this application meets Q1·100 / R. dc ≥6.0, here Q1 is substituted into the formula as a percentage.
[0065] In some embodiments, the lithium-ion battery of this application also meets Q2·100 / R dc ≥7.0, here Q2 is substituted into the formula as a percentage.
[0066] In some embodiments, the lithium-ion battery of this application has a median discharge voltage V≥2.98V when continuously discharged at a rate of 3C or higher in an environment with a temperature of -20°C or below.
[0067] In some embodiments, the thickness expansion rate t of the lithium-ion battery of this application is ≤5% after being placed in an environment with a temperature of 60°C for 7 days.
[0068] In some embodiments, the surface of the negative electrode has a solid electrolyte interface (SEI) film, which is tested by X-ray photoelectron spectroscopy (XPS). The area ratio of LiF in the SEI film is 20% to 40% based on the total F1s peak area; the area ratio of ROSO2Li is 10% to 25% based on the total S2p peak area, and it contains BO bonds. Here, the B1s binding energy is between 191.2 eV and 191.8 eV.
[0069] In some embodiments, the surface of the positive electrode has a positive electrolyte interface film (CEI), which is tested by X-ray photoelectron spectroscopy (XPS). The area ratio of Li3PO4F in the CEI film is 5% to 15% based on the total P2p peak area, and the area ratio of CF bonds is 8% to 20% based on the total F1s peak area.
[0070] In the above embodiments, ε in the above formula s ε i P, Q1, Q2, R dc All of these are dimensionless characteristic coefficients. Specifically, they reveal the relative quantitative relationship between parameters using numerical values. In this case, dimensions are not considered, or they are regarded as dimensionless.
[0071] Combination Figures 1 to 3 As shown in this embodiment, the lithium-ion battery further includes a casing, in which a positive electrode and a negative electrode are encapsulated. Specifically, the lithium-ion battery includes a cylindrical casing 2, the interior of which houses the battery cell, with the top being the positive terminal 1 and the bottom being the negative terminal 12. A positive electrode post 11 is disposed on the positive terminal 1. Specifically, Figure 2 A schematic diagram of the lithium-ion battery structure in this application is shown. Figure 3 A schematic diagram of the lithium-ion battery described in this application is shown. The positive electrode 5, negative electrode 3, and electrolyte membrane 4 are shown as follows: Figure 3 The layers are stacked and then wound to form... Figure 2 The cylindrical battery cell 10 shown is initially wound to the electrode end at the cylindrical axis, and ends to the electrode end on the outer surface of the cylinder after winding. The positive electrode 5 includes a strip-shaped positive electrode foil, a positive electrode coating on the surface of the strip-shaped positive electrode foil, and a first empty foil area. The negative electrode 3 includes a strip-shaped negative electrode foil, a negative electrode coating on the surface of the strip-shaped negative electrode foil, and a second empty foil area. The first and second empty foil areas are perpendicular to the winding direction and are formed into the top or bottom end face of the lithium-ion battery by methods such as flattening or folding.
[0072] Furthermore, embodiments of this disclosure also provide an electrical device, including a lithium-ion battery for providing power as described in this application.
[0073] The present invention will be further explained and illustrated below with reference to embodiments.
[0074] This embodiment 1 provides a lithium-ion battery. Preparation of positive electrode sheet: The positive electrode active material is NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2); A positive electrode slurry was prepared by mixing positive electrode active material, conductive carbon black (SP), carbon nanotubes (CNT), and polyvinylidene fluoride (PVDF) in a mass ratio of 96.5:1.0:0.5:2.0. The positive electrode slurry was then coated onto an aluminum foil with a thickness of 15 μm, and after rolling and slitting, a positive electrode sheet was obtained. The areal density of the positive electrode active material layer on one side was 20 mg / cm³. 2 The compaction density of the positive electrode sheet is 3.55 g / cm³. 3 .
[0075] Preparation of negative electrode sheet: The negative electrode active material consists of artificial graphite and hard carbon in a mass ratio of 90:10, wherein the median particle size D of the artificial graphite is... 50 It has a thickness of 12 μm and a compaction density of 1.70 g / cm³. 3 Median particle size D of hard carbon 50 It has a diameter of 7 μm and a specific surface area of 3.5 m². 2 / g; A negative electrode slurry was prepared by dispersing the negative electrode active material, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in deionized water at a mass ratio of 96.5:1.0:1.2:1.3. The slurry was then coated onto a copper foil with a thickness of 8 μm. The temperature gradient of the coating oven was controlled to create a porosity gradient in the negative electrode active material layer. After rolling and slitting, the positive electrode sheet was obtained, and the negative electrode sheet was obtained after rolling. In controlling the temperature gradient of the coating oven, the inlet temperature is 80℃, the middle section temperature is 100℃, and the outlet temperature is 120℃. This allows the surface layer, farther from the copper foil, to dry faster and have higher porosity, while the bottom layer, closer to the copper foil, dries slower and has lower porosity. Here, the compaction density of the negative electrode sheet is 1.68 g / cm³. 3 The surface porosity of the negative electrode sheet is 32%, the bottom porosity is 24%, and the porosity gradient parameter of the negative electrode sheet is 4.76. The specific calculation formula is (32-24) / 1.68=4.76.
[0076] Preparation of electrolytes: In a drying room with a dew point temperature T ≤ -40℃, ethylene carbonate (EC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), and hydrofluoroether (HFE) are mixed and stirred thoroughly in a volume ratio of 15:55:15:15 to serve as the base solvent. Here, the molecular weight of HFE is 300 to 500.
[0077] 0.8 mol / L lithium hexafluorophosphate (LiPF6) and 0.3 mol / L lithium bisfluorosulfonylimide (LiFSI) were added sequentially to the base solvent and stirred until completely dissolved to prepare a dual-salt electrolyte.
[0078] Then, 1% vinylene carbonate (VC), 1.5% vinyl sulfate (DTD), and 1% tris(trimethylsilyl)borate (TMSB) were added according to the total mass of the electrolyte, and the mixture was stirred for 30 minutes to obtain the electrolyte.
[0079] Preparation of the diaphragm: A 12μm thick polyethylene (PE) film was used as the base film, and a 4μm thick ceramic coating (Al2O3) was coated on the base film.
[0080] Assemble lithium-ion batteries: The positive electrode, separator, and negative electrode are wound into a core, inserted into the battery casing, injected with the corresponding electrolyte, sealed, and then formed. Here, the lithium-ion battery is a 21650 model battery with a height of 65.0 mm and an outer diameter of 21.0 mm.
[0081] Transformation and Division: First stage: Under the condition of -10℃, constant current charging at a charging rate of 0.05C for 2 hours; Second stage: Under the condition of 25℃, charge at a constant current of 0.15C to 3.5V; The third stage: Under the condition of 45℃, charge at a constant current rate of 0.25C to 4.2V, and then switch to constant voltage charging to 0.03C.
[0082] After formation, the lithium-ion battery is subjected to capacity testing and aging to obtain the lithium-ion battery of Example 1.
[0083] Example 2 Example 2 provides a lithium-ion battery. The difference between this example and Example 1 is that the negative electrode active material includes artificial graphite and hard carbon in a mass ratio of 85:15, and the compaction density of the negative electrode is 1.65 g / cm³. 3 The surface porosity of the negative electrode sheet is 33%, the bottom porosity is 25%, and the porosity gradient parameter of the negative electrode sheet is 4.85, calculated as (33-25) / 1.65=4.85. In the electrolyte, the volume ratio of EC, EMC, FEC, and HFE is 10:60:15:15, LiPF6 is 0.6 mol / L, LiFSI is 0.5 mol / L, VC accounts for 2% of the total electrolyte mass, DTD accounts for 2.5% of the total electrolyte mass, and TMSB accounts for 1.5% of the total electrolyte mass. Other parameters are the same as in Example 1.
[0084] Example 3 Example 3 provides a lithium-ion battery. The difference between this example and Example 1 is that the negative electrode active material includes artificial graphite and hard carbon in a mass ratio of 95:5, and the compaction density of the negative electrode is 1.70 g / cm³. 3 The surface porosity of the negative electrode is 30%, the bottom porosity is 22%, and the porosity gradient parameter of the negative electrode is 4.71, calculated as (30-22) / 1.70=4.71. In the electrolyte, the volume ratio of EC, EMC, FEC, and HFE is 20:50:10:20, LiPF6 is 1 mol / L, LiFSI is 0.2 mol / L, VC accounts for 0.5% of the total electrolyte mass, DTD accounts for 0.5% of the total electrolyte mass, and TMSB accounts for 0.3% of the total electrolyte mass. Other parameters are the same as in Example 1.
[0085] Comparative Example 1 Comparative Example 1 provides a lithium-ion battery. The difference between this comparative example and Example 1 is that no hard carbon is added to the negative electrode active material, and the compaction density of the negative electrode is 1.66 g / cm³. 3The surface porosity of the negative electrode sheet is 38%, the bottom porosity is 26%, and the porosity gradient parameter of the negative electrode sheet is 7.23, calculated as (38-26) / 1.66=7.23. The volume ratio of EC, EMC, and FEC is 30:60:10, no HFE is added, LiPF6 is 1 mol / L, no LiFSI, DTD, and TMSB are added. During formation and capacity testing, at 25°C, the electrode is charged at a constant current rate of 0.1C to 3.5V, then charged at a rate of 0.2C to 4.2V, and finally charged at a constant voltage rate to 0.05C. Other aspects are the same as in Example 1.
[0086] Comparative Example 2 Comparative Example 2 provides a lithium-ion battery. The difference between this comparative example and Example 1 is that no hard carbon is added to the negative electrode active material, and the compaction density of the negative electrode is 1.72 g / cm³. 3 The surface porosity of the negative electrode sheet is 25%, the bottom porosity is 23%, and the porosity gradient parameter of the negative electrode sheet is 1.16, calculated as (25-23) / 1.72=1.16. The volume ratio of EC, EMC, FEC, and HFE is 20:55:15:10, LiPF6 is 1 mol / L, and no LiFSI or TMSB is added. During formation and capacity testing, at a temperature of 25°C, the electrode is charged at a constant current rate of 0.1C to 3.5V, then charged at a constant voltage rate of 0.2C to 4.2V, and finally charged at a constant voltage rate to 0.05C. Other procedures are the same as in Example 1.
[0087] Comparative Example 3 Comparative Example 3 provides a lithium-ion battery. The difference between this comparative example and Example 1 is that the bottom porosity of the negative electrode sheet is 26%, and the porosity gradient parameter of the negative electrode sheet is 3.57, which is specifically calculated as (32-26) / 1.68=3.57. Everything else is the same as in Example 1.
[0088] Comparative Example 4 Comparative Example 4 provides a lithium-ion battery. The difference between this comparative example and Example 1 is that no hard carbon is added to the negative electrode active material, and the compaction density of the negative electrode is 1.72 g / cm³. 3 The bottom layer porosity of the negative electrode sheet is 26%, and the porosity gradient parameter of the negative electrode sheet is 3.49, which is specifically calculated as (32-26) / 1.72=3.49. Everything else is the same as in Example 1.
[0089] The negative electrode parameters of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1, including the mass ratio of artificial graphite to hard carbon, compaction density, surface porosity of the negative electrode, bottom porosity of the negative electrode, and porosity gradient parameters of the negative electrode.
[0090]
[0091] Table 1 The electrolyte parameters of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 2, including the volume ratio of EC, EMC, FEC and HFE, the concentration of LiPF6, the concentration of LiFSI, the percentage of VC in the total electrolyte mass, the percentage of DTD in the total electrolyte mass, and the percentage of TMSB in the total electrolyte mass.
[0092]
[0093] Table 2 The lithium-ion batteries of Examples 1 to 3 and Comparative Examples 1 to 4 were tested accordingly.
[0094] Pre-treatment of test batteries Disassembly was performed in an argon glove box with H2O < 0.1 ppm and O2 < 0.1 ppm. The electrode was cleaned, immersed in dimethyl carbonate (DMC) at 25°C for 15 min, repeated 3 times, and then vacuum dried at 80°C for 4 h. The cross-section was prepared by argon ion polishing (CP) at a voltage of 5 kV and a cooling temperature of -100°C.
[0095] X-ray photoelectron spectroscopy (XPS) was used to determine the chemical composition of the interface film. A monochromatic AlKα X-ray source (1486.6 eV) was used for XPS interface film composition detection, with the pass energy set to 50 eV. Charge calibration was performed using the C1s peak at 284.8 eV. Ar24-kJ / k2 was used to analyze the negative electrode. + Ion etching was performed at a rate of 0.5 nm / min, and F1s, S2p, and B1s spectra were collected every 2 nm of etching. P2p and F1s spectra were directly collected from the positive electrode to obtain the chemical composition of the interface film on the positive and negative electrode surfaces.
[0096] For the chemical bond assignment of the interface film, the characteristic peak positions corresponding to each chemical bond in the solid electrolyte interphase (SEI) film formed on the negative electrode surface are determined according to the following criteria: Lithium fluoride (LiF): The binding energy corresponding to the F1s peak is 684.8 ± 0.2 eV; Organic lithium sulfonate (ROSO2Li): The binding energy corresponding to the S2p peak is 167.5 ± 0.3 eV; Boron-oxygen bond (BO bond): The binding energy corresponding to the B1s peak is 191.5 ± 0.3 eV.
[0097] The characteristic peak positions corresponding to each chemical bond in the positive electrode electrolyte interphase (CEI) film formed on the positive electrode surface are determined according to the following criteria: Lithium fluorophosphate (Li3PO4F): The binding energy corresponding to the P2p peak is 134.5 ± 0.2 eV; Carbon-fluorine bond (CF bond): The binding energy corresponding to the F1s peak is 688.5 ± 0.2 eV.
[0098] The relative proportions of each component in the interfacial film are calculated by integrating the peak areas of the corresponding characteristic peaks, and then normalized based on the total peak area of all spectral peaks of that element.
[0099] Time-of-flight secondary ion mass spectrometry (TOF-SIMS) was used to analyze the solid electrolyte interface film on the negative electrode surface. A TOF-SIMS IV instrument was used with Bi3+ at an energy of 25 keV. + As an analytical ion source, Cs with an energy of 10 keV was used. + The area of the sputtering region was set to 300 × 300 μm as the sputtering ion source. 2 In negative ion collection mode, LiF was recorded respectively. - (Mass-to-charge ratio m / z is 25), CH2OCO2Li - (Mass-to-charge ratio m / z is 83), BO2 - The characteristic ion signal intensity (with a mass-to-charge ratio m / z of 43) varies with sputtering time, thus reflecting the gradient distribution structure of the solid electrolyte interface film along the depth direction.
[0100] The porosity gradient of the negative electrode sheet was measured using a focused ion beam (FIB) technique to prepare an ultrathin section of the negative electrode sheet with a thickness of approximately 100 nm. The cross-sectional morphology was observed using a scanning electron microscope (SEM) in backscattered electron mode. The cross-sectional image was divided into three regions along the thickness direction: upper, middle, and lower. The upper region extends from the electrode surface to one-third of the thickness, and the lower region extends from two-thirds of the thickness to the interface between the current collector and the active material. ImageJ software was used to binarize the images of each region, and threshold values were set to distinguish between active material particles and pores. The porosity of each of the three regions was then calculated.
[0101] Here, the surface porosity of the negative electrode sheet is the porosity of the upper region, and the bottom porosity of the negative electrode sheet is the porosity of the lower region.
[0102] The battery internal resistance test was conducted at 25°C, and the battery state of charge (SOC) was adjusted to 50% before the test.
[0103] In the AC internal resistance test, electrochemical impedance spectroscopy (EIS) was used for determination, with the test frequency set at 1 kHz and the AC disturbance voltage amplitude at 5 mV.
[0104] In the DC internal resistance test, the battery was discharged at a rate of 0.2 C for 10 seconds, and the corresponding terminal voltage V1 was recorded. Continue discharging at a 1 C rate for 10 seconds and record the corresponding terminal voltage V2. DC internal resistance R dc The ratio of voltage difference to current difference is used for calculation, and the formula is as follows: R dc =|V1-V2| / |I2-I1| Where I1 is the discharge current corresponding to a 0.2C rate, and I2 is the discharge current corresponding to a 1C rate.
[0105] For the low-temperature discharge test, the battery was placed in a -20℃ constant temperature test chamber and left to stand for 4 hours until the battery reached thermal equilibrium. Then, it was discharged at a constant current rate of 3C to the cutoff voltage of 2.5V, and the discharge capacity under this condition was recorded. The low-temperature capacity retention rate is C1 / C2×100%, and the median discharge voltage is the integral average of voltage over time during the discharge process; where C1 is the discharge capacity at -20℃ and C2 is the discharge capacity at 0.2C rate at 25℃.
[0106] High-temperature cycling test: In a constant temperature environment of 45℃±2℃, the single-cycle charge-discharge process is as follows: Charge at a constant current rate of 1C to 4.2V, then switch to constant voltage charging until the charging current drops to 0.05C. After charging is complete, let it stand for 5 minutes. Discharge at a constant current rate of 1C until the cutoff voltage of 2.5V, and let stand for 5 minutes after the discharge is completed; this completes one cycle.
[0107] The battery discharge capacity is recorded once every 100 cycles to evaluate the battery's high-temperature cycling performance.
[0108] The pulse discharge test was conducted at 25°C and a battery state of charge (SOC) of 50%. The battery was pulse-discharged at a 10C rate for 1 second, followed by a 59-second rest period; this constituted one test cycle. The real-time voltage curve during the pulse discharge was recorded. The difference between the terminal voltage at the end of the first second of the pulse discharge and the resting voltage before the pulse started was taken as the pulse voltage drop, used to characterize the battery's voltage response characteristics under high-current pulse discharge.
[0109] After conducting the above tests in Examples 1 to 3 and Comparative Examples 1 to 4, the corresponding data were obtained. These included the area percentages of LiF, ROSO2Li, and BO bonds in the SEI film; the area percentages of Li3PO4F and CF bonds in the CEI film; and Q1·100 / R. dc The value of Q2·100 / R dc The value of (ε) s -ε i The value of ) / P. Here, the relevant data is shown in Table 3.
[0110]
[0111] Table 3 After conducting the above tests in Examples 1 to 3 and Comparative Examples 1 to 4, the corresponding data were obtained. AC internal resistance R ac DC internal resistance R dc Low-temperature capacity retention, median voltage, pulse voltage drop, and high-temperature cycling capacity retention are all measured. The relevant data are shown in Table 4.
[0112]
[0113] Table 4 Referring to Table 4 above, comparing Comparative Example 1 and Comparative Example 2, it can be seen that in Comparative Example 1, the electrolyte is a conventional single-salt, single-solvent electrolyte, and its low-temperature capacity retention rate is only 35%, while its high-temperature cycling capacity retention rate is 62%. In Comparative Example 2, after adding LiPF6, LiFSI, a quaternary solvent, VC, and DTD, the AC internal resistance R... ac The DC internal resistance R decreases from 12mΩ to 9mΩ. dc The electrolyte strength decreased from 22 mΩ to 16 mΩ, and the low-temperature capacity retention increased to 48%, while the high-temperature cycling capacity retention increased to 71%. This demonstrates that the electrolyte and porosity gradient in Comparative Example 2 can improve performance over a wide temperature range.
[0114] Referring to Tables 3 and 4 above, a comparison of Comparative Examples 2 and 3 reveals that while the electrolyte formulations of Comparative Examples 2 and 3 are the same, Comparative Example 2 employs a conventional single-stage formation at 25°C, while Comparative Example 3 utilizes a three-stage gradient formation. Specifically, in Comparative Example 3, the LiF content in the SEI film increased from 15% to 28%, ROSO2Li increased from 12% to 18%, and 10% BO bonds appeared for the first time; the Li3PO4F content in the CEI film increased from 3% to 10%. Correspondingly, the low-temperature capacity retention increased from 48% to 62%, and the high-temperature cycling capacity retention increased from 71% to 75%. Therefore, this demonstrates that the three-stage gradient formation can further achieve a performance leap.
[0115] Referring to Tables 3 and 4 above, a comparison of Comparative Example 3, Comparative Example 4, and Example 1 shows that Comparative Example 4 has the same formation method and electrolyte formulation as Comparative Example 3. However, the negative electrode of Comparative Example 4 does not contain hard carbon, and the porosity gradient is achieved through physical rolling rather than temperature control. The low-temperature capacity retention rate of Comparative Example 4 is 58%, lower than the 62% of Comparative Example 3, and the AC internal resistance R... ac and DC internal resistance R dc This is higher than Comparative Example 3. In Example 1, after adding 10% hard carbon to the negative electrode and forming a true porosity gradient, the low-temperature capacity retention was further improved to 72%, and the median voltage reached 3.08V. Therefore, it is shown that the microporous defect sites of hard carbon can reduce the low-temperature lithium intercalation barrier, while the porosity gradient can optimize the ion transport path, resulting in a synergistic effect between the two.
[0116] As shown in Tables 3 and 4 above, Example 1 significantly outperforms Comparative Examples 1 to 4 in both low-temperature capacity retention and high-temperature cycling capacity retention. Here, Comparative Example 1 only differs from Comparative Example 2 in that it lacks a porosity gradient, and in Comparative Example 4, no hard carbon was added to the negative electrode active material. The fact that Example 1's performance is far superior to Comparative Examples 1 to 4 indicates that the parameters, structures, and coupling relationships are not simply additive.
[0117] The foregoing description and accompanying drawings fully illustrate embodiments of the present disclosure to enable those skilled in the art to practice them. Other embodiments may include structural and other changes. The embodiments represent only possible variations. Individual components and functions are optional unless explicitly required, and the order of operation may vary. Parts and features of some embodiments may be included or substituted for parts and features of other embodiments. Embodiments of the present disclosure are not limited to the structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from its scope. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A lithium-ion battery, characterized in that, include: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode active material layer includes artificial graphite and hard carbon. The negative electrode active material layer has a porosity gradient in the thickness direction and satisfies the following relationship: 3.5≤(ε s -e i ) / P≤5.5; Where, ε s ε represents the surface porosity of the negative electrode sheet, expressed as a percentage (%). i P represents the bottom layer porosity of the negative electrode sheet, expressed as %, while P represents the compacted density of the negative electrode sheet, expressed as g / cm³. 3 ; Electrolytes include organic solvents, lithium salts, and additives, wherein the organic solvents include ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate, and hydrofluoroether; the lithium salts include lithium hexafluorophosphate and lithium difluorosulfonylimide; and the additives include ethylene carbonate, ethylene sulfate, and tris(trimethylsilyl)borate.
2. The lithium-ion battery according to claim 1, characterized in that, The mass ratio of artificial graphite to hard carbon is 85:15 to 95:
5.
3. The lithium-ion battery according to claim 2, characterized in that, The surface porosity of the negative electrode sheet is 28% to 35%, the bottom porosity is 20% to 28%, and the compacted density of the negative electrode sheet is 1.60 g / cm³. 3 Up to 1.75 g / cm 3 .
4. The lithium-ion battery according to claim 3, characterized in that, The surface layer of the negative electrode sheet extends from the surface of the negative electrode sheet to 1 / 3 of the thickness of the negative electrode active material layer, while the bottom layer of the negative electrode sheet extends from 2 / 3 of the thickness of the negative electrode active material layer to the interface between the current collector and the negative electrode active material layer.
5. The lithium-ion battery according to any one of claims 1 to 4, characterized in that, The volume ratio of ethylene carbonate, methyl ethyl carbonate, fluoroethylene carbonate and hydrofluoroether is 10:50:20:20 to 20:60:10:
10.
6. The lithium-ion battery according to claim 5, characterized in that, The concentration of lithium hexafluorophosphate is 0.6 mol / L to 1.0 mol / L, and the concentration of lithium difluorosulfonylimide is 0.2 mol / L to 0.5 mol / L.
7. The lithium-ion battery according to claim 5, characterized in that, Vinyl carbonate accounts for 0.5% to 2.0% of the total mass of the electrolyte, vinyl sulfate accounts for 0.5% to 2.5% of the total mass of the electrolyte, and tris(trimethylsilyl)borate accounts for 0.3% to 1.5% of the total mass of the electrolyte.
8. The lithium-ion battery according to any one of claims 1 to 4, characterized in that, The lithium-ion battery is formed through three sequential charging stages, in which the ambient temperature and charging rate increase in each stage.
9. The lithium-ion battery according to claim 8, characterized in that, The formation process of lithium-ion batteries includes the following three charging stages: Phase 1: Under the first temperature environment, constant current charging at the first charging rate for a preset duration; Second stage: Under the second temperature environment, charge at a constant current at a second charging rate to the first preset voltage; The third stage: Under the third temperature environment, constant current charging is performed at the third charging rate until the second preset voltage is reached, and then constant voltage charging is switched until the charging current drops to the cutoff current, thus completing the formation.
10. An electrical appliance, characterized in that, Including the lithium-ion battery as described in any one of claims 1 to 9.